Effectiveness and Efficiency Analysis: Budget Revenue and Regional Spending in Bengkulu Province, Period 2017-2021 - Mutiara Rizki Utami; Yefriza Yefriza (Fakultas Ekonomi Dan Bisnis, Universitas Bengkulu, 2023)
Government performance areas can be assessed through evaluation performance, with finance analysis to implement the existing APBD prepared and implemented. Study This aims To analyze the effectiveness and efficiency of the management budget income and expenditure regional budget (APBD) of Bengkulu Province for the 2017-2021 period. The research methods used are method descriptive quantitative using secondary data from report realization of the Bengkulu Province APBD for the 2017-2021 period obtained from various agency-related parties, such as the Financial Service Bengkulu Province, Bureau of Statistics Bengkulu Province, and reports budget officially issued by the government area. Analytical tools used are ratio effectiveness and efficiency, starting from reduction data, presentation data, and withdrawal conclusion/verification. Research results show that the level of effectiveness management of the Bengkulu Province APBD for the 2017-2021 period averaged 91 %, which shows that management of the Bengkulu Province APBD has effectively achieved revenue and expenditure targets area. Efficiency level Bengkulu Province APBD management for the 2017-2021 period averaged 69 %, which shows that the Bengkulu Province APBD management has been completed efficiently in optimizing its resources.